2022
DOI: 10.2217/epi-2022-0228
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of VTRNA2-1 / nc886 is stable across populations, monozygotic twin pairs and in majority of tissues

Abstract: Aims & methods: The aim of this study was to characterize the methylation level of a polymorphically imprinted gene, VTRNA2-1/ nc886, in human populations and somatic tissues.48 datasets, consisting of more than 30 tissues and >30,000 individuals, were used. Results: nc886 methylation status is associated with twin status and ethnic background, but the variation between populations is limited. Monozygotic twin pairs present concordant methylation, whereas ∼30% of dizygotic twin pairs present discordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…S4). Human studies have shown that methylation at CoRSIVs is stable for years in the same individual [ 12 , 22 , 23 ]. It is possible, therefore, that profiling CoRSIV methylation in peripheral blood DNA of calves could someday be utilized to identify those individuals most likely to exhibit traits favorably associated with productivity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Human studies have shown that methylation at CoRSIVs is stable for years in the same individual [ 12 , 22 , 23 ]. It is possible, therefore, that profiling CoRSIV methylation in peripheral blood DNA of calves could someday be utilized to identify those individuals most likely to exhibit traits favorably associated with productivity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore performed DNAmethylation profiling on biopsies taken from all genotypes and animals at 10 days of age (i.e., before weaning). We used ear clips as they are minimally invasive for young mice and are similar to tissues used to identify early-life epigenetic signatures in humans [50][51][52][53][54][55] . We used Illumina Infinium Mouse Methylation BeadChips to quantify DNA methylation state at ~285,000 CpG sites that included CpGs in all annotated genes, functional RNAs, and cis-regulatory regions of the mouse genome.…”
Section: Trim28-dependent Developmental Heterogeneity Primes Cancer O...mentioning
confidence: 99%
“…Aberrantly methylated iDMRs were defined as iDMRs showing differentially methylated levels in at least two consecutive probes within iDMRs which included at least four significant probes [19]. The VTRNA2-1:DMR was considered as insignificant because it has been shown to be polymorphically imprinted in general population, showing frequent hypomethylation with various degrees [29]. We considered each patient as having MLID if showing aberrant methylation in one or more additional iDMRs other than the disease-related iDMRs.…”
Section: Gwma and Data Analysismentioning
confidence: 99%